CONTEMPORARY BOOK STUDIES IN FRANCE: THE INTERFACE AMONG RESEARCH, TRAINING AND PROFESSIONAL PRACTICE - DECAUX, SYLVIE (Knygotyra, 2010)
The purpose of this paper is to present the situation of book studies in France today, in particular the interface between academic research and vocational training, and its development over the past 15 to 20 years. It provides an overview of places of learning devoted to the book, and of the various French institutions involved in research and/or training in this field. It discusses the leading figures and presents a map of the discipline, both historical and geographical. The impact on professional practice is also examined, as it becomes clear that book studies, through their very nature, necessarily include a practical and material component.